PENYULUHAN NYERI PUNGGUNG BAWAH DAN NYERI KEPALA AKIBAT BEKERJA DARI RUMAH - Rima Anindita Primandari; Andini Aswar (Universitas Trisakti, 2023)
The COVID-19 pandemic has affected various aspects of people's lives. To prevent transmission, one of the policies made is to Work From Home (WFH) which allows workers to work more flexibly and still meet the requirements for physical distancing. However, WFH can also cause a decrease in physical activity in workers and have a negative impact on workers' health. Low back pain (LBP) and headache are complaints that are often felt by workers due to WFH. The purpose of this Community Service activity is to increase public knowledge about low back pain and headaches due to WFH. This activities is carried out online using a zoom meeting in the form of webinar with the lecture method using PPT, questions and answers, and discussions as well as sharing experiences about LBP and headaches. The target participants are 30 people. The participants seemed serious and enthusiastic in participating in the webinar as evidenced by the many questions asked. Although the participants' education was quite good, knowledge about LBP and headaches was still lacking.